Persepsi Konsumen terhadap In-Store Experience dan Pengaruhnya terhadap Minat Beli: Studi Kasus pada Konsumen OH! SOME Tunjungan Plaza Surabaya - Yulianti, Raihan Adillah; Muharomah, Nadya Aurelia; Cahya Kamila, Kania Agustin; Islamiyah, Nuruddina; Putri Denita, Sabrina; Hidayat Nugroho, Rusdi (Ikatan Da'i Indonesia, 2026)
This study aims to examine how in store experience shapes consumer perceptions and purchase intentions at the OHSOME store in Tunjungan Plaza Surabaya. The research problem arises from the high number of visitors that is not aligned with the conversion rate, indicating the need for a deeper understanding of the shopping experiences perceived by consumers inside the store. This study employs a qualitative approach with an interpretive paradigm through semi structured interviews, non participant observation, and documentation, and the data are analyzed using the Miles, Huberman, and Saldana model. The findings show that store atmosphere, which includes lighting, scent, music, and cleanliness, together with spatial arrangement, product presentation, staff interaction, and overall shopping comfort, contributes to the formation of positive consumer experiences that encourage longer product exploration and increase the likelihood of both planned and impulsive purchases. Attractive product displays and the availability of testers serve as key drivers of purchase intention, while constraints are observed in the absence of clear category signage and long cashier queues during peak periods. This study contributes to the development of in store experience research in the context of local lifestyle retail and offers practical implications for improving visual navigation and service efficiency.